P644 Analyzing the genomes of neisseria gonorrhoeae isolates using a novel integrated bioinformatic pipeline: Gen2Epi. (14th July 2019) - Parmar, Nidhi; Singh, Reema; Martin, Irene; Perera, Sumudu; Demczuk, Walter; Kusalik, Anthony; Minion, Jessica; Dillon, Jo-Anne
Abstract : Background: Whole genome sequencing (WGS) is a high-resolution approach for tracking the transmission and antimicrobial susceptibility (AMS) of Neisseria gonorrhoeae (Ng). Multiple bioinformatics tools currently used for the analysis of WGS data for Ng complicate their application in clinical settings. We determined the genomic epidemiology and AMS of Ng from Saskatchewan (SK) using our integrated pipeline, Gen2Epi, previously validated on 1484 publicly available Ng genome datasets. Methods: WGS was performed on 99 Ng isolates (2017–2018) from SK submitted to the Roy Romanow Provincial Laboratory. Genomic DNA was isolated using the DNAeasy mini kit (QIAGEN) and sequenced using MiSeq (Illumina). MICs were determined by agar dilution. Gen2Epi includes read assembly, scaffolding, strain typing (ST) by MLST and NG-MAST, plasmid identification, and, identification of mutations in antibiotic resistance genes by NG-STAR. Results: Nine MLST/NG-MAST/NG-STAR (M/M/S) STs comprised 75.6% (75/99) of the isolates; other M/M/S STs (24.3%, 24/99) comprised single isolates. M/M/S ST 1901/10451/90 predominated (21.3%, 21/99), carrying mosaic penA type 34.001 and mutations in mtrR/porB/ponA/gyrA/parC . These isolates were chromosomally resistant to penicillin (38%, 8/21), tetracycline (95.2%, 20/21), and ciprofloxacin (90%, 19/21); they were susceptible to ceftriaxone and 38% (8/21) had cefixime MICs of 0.125 mg/L. The second-most prevalent ST was 1584/7638/160 (18/99); most of these isolates (16/18) were susceptible to all antibiotics. Overall, 57.6% (57/99) of the isolates were tetracycline resistant; 29.8% (17/57) of these were from Regina and carried a tetM gene (M/M/S ST 12462/5985/42). One sporadic isolate was azithromycin resistant (23S rRNA-A2059G), carried tetM and was M/M/S ST 7822/304/515. Conclusion: Gen2Epi is a one-stop pipeline that both assembles and annotates raw reads and simplifies the analysis of transmission markers and AMS in Ng. We showed the emergence of M/M/S ST 1901/10451/90 as the predominant ST in SK. NG-MAST ST 10451 is similar (≤2bp) to ST 1407 which is implicated in reduced susceptibility to cefixime. Disclosure: No significant relationships.